Various modes of cell death induced by DNA damage - Surova, O; Zhivotovsky, B (Oncogene, 2013)
The consequences of DNA damage depend on the cell type and the severity of the damage. Mild DNA damage can be repaired with or without cell-cycle arrest. More severe and irreparable DNA injury leads to the appearance of cells that carry mutations or causes a shift towards induction of the senescence or cell death programs. Although for many years it was argued that DNA damage kills cells via apoptosis or necrosis, technical and methodological progress during the last few years has helped to reveal that this injury might also activate death by autophagy or mitotic catastrophe, which may then be followed by apoptosis or necrosis. The molecular basis underlying the decision-making process is currently the subject of intense investigation. Here, we review current knowledge about the response to DNA damage and subsequent signaling, with particular attention to cell death induction and the molecular switches between different cell death modalities following damage.